Ethics in health administration - "Morrison, Eileen E" (London, 2011)
Given the many new advances in technology as well as the roll out of the Affordable Care Act, today$1 (Bs healthcare administrators require a strong foundation in practice-based ethics to confront the challenges of the current healthcare landscape. Ethics in Health Administration, Third Edition translates the principles and practice of ethics into usable information for application to the real world of healthcare administration and the critical issues faced by today$1 (Bs healthcare administrators. The Third Edition is an extensive revision that addresses the many new ethical challenges administrators will face, in light of the Affordable Care Act (ACA). Careful attention is given to the ACA concept of patient-centered care through safety and quality standards. Thoroughly updated chapters throughout as well as a two new chapter on the Affordable Care Act (ACA) of 2010 and on Public Health, make this text relevant to the issues facing today$1 (Bs healthcare administrator. Fictional cases based on real-world events help to emphasize chapter content and create interest for the learner. Each chapter includes points to ponder, summary statements, Web sites, and additional resources to further enhance learning. The author$1 (Bs reader-friendly writing style easily engages students while challenging them to think critically.s
Keywords: Health service administration-Moral & ethical aspects